Factors associated with self-injurious behavior among adolescents assisted by a Psychosocial Care Center in the Northeast of Brazil (Research, Society and Development, 2021)
Self-mutilation is a self-injurious behavior against oneself, usually associated with trauma or experiences arising from emotional and affective overload, resulting in small and/or large cuts on the body. The present study aims to identify and analyze the factors that may be associated with self-injury in adolescents. In addition, to understand the damage that self-injury can cause in the occupational performance in daily activities of these adolescents. This is an exploratory study with a qualitative approach, carried out with eight (8) adolescents in a Child and Youth Psychosocial Care Center (CAPSij) in Maceió. We used the FunctionalAssessmentof Self-Mutilation Behavior (FASM) scale and a semi-structured interview based on the American Occupational Therapy Association (AOTA). To analyze the data we used Bardin's content analysis theory. The results showed association between self-harm with affective-emotional and suicide attempt by most of the adolescents. In relation to occupational performance we observed total or partial disruption when performing daily activities such as leisure, daily life activities, in social relationships, and at school.  Given this bleak scenario, we suggest that these adolescents could have specialized care and comprehensive attention to help them empower their routine and improve their emotional, affective and productive quality of life in their daily lives.